Novel P2Y12 Receptor Antagonists - Prasugrel and Ticagrelor. Systematic Review, Indirect Comparison to Clopidogrel in Cardiovascular Disease, Design of a Randomized Controlled Trial - Steiner-Boeker, Sabine (Université d'Ottawa / University of Ottawa, 2011)
Antiplatelet therapy with clopidogrel is widely used in patients with coronary artery disease, but the recent development of the new P2Y12 receptor antagonists prasugrel and ticagrelor will increase treatment options. An overview of systematic reviews was performed to summarize available evidence on clopidogrel. Current data on prasugrel and ticagrelor were identified by a systematic review and used for an indirect treatment comparison (ITC) of the drugs against each other and versus placebo in the absence of head-to-head clinical trials. Adjusted indirect comparison according to Bucher, Bayesian methods for mixed treatment comparisons using Winbugs, and generalized linear mixed models using SAS were employed for ITC, yielding almost identical results: prasugrel was favored regarding stent thrombosis and ticagrelor regarding major bleeding. However, substantial differences in trial design were identified, demanding caution when interpreting these results. On the basis of the obtained results, a randomized controlled trial was designed within the gap of current evidence.
Keywords: Antiplatelet therapy; ADP antagonists; Indirect treatment comparison; Meta-analysis